Analisis Bibliometrik Pengembangan Media Pembelajaran Pop Up Book di Madrasah Ibtidaiyah pada Tahun 2019-2024 - Titania Amilia Putri; Santiani (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research aims to analyse the development of Pop Up Book Learning Media in Madrasah Ibtidaiyah in 2019-2024 using bibliometric computational mapping analysis method. Publish or Perish software was used to collect publication data from the Google Scholar database using the keywords "Learning Media", "Pop Up Book", "" AND "Madrasah Ibtidaiyah" OR "MI". This search resulted in 55 articles. These results show that the number of publications related to this topic from the range of 2019-2024 is still small, with an average number of publications of 1.67. Then the highest number of publications on Pop Up Book Learning Media in Madrasah Ibtidaiyah was obtained in 2023 with 4 articles, while the lowest number of publications was obtained in 2019, 2021 and 2022 with 0 articles. Keyword co-occurrence analysis using VOSViewer resulted in 32 terms grouped into 5 clusters. Network and density visualisation shows several keywords that frequently appear, namely Pop Up Book, Book, and Media Pop Up Book. In addition, the overlay visualisation illustrates keywords that have been trending in recent years Pop Up Book, Book, and Media Pop Up Book. Thus, future studies need to focus on Pop Up Book learning media and on various subjects in Madrasah Ibtidaiyah.